Urgensi inovasi pembelajaran pada mata pelajaran sejarah - Hilmiah, Anis Syatul (Oetoesan-Hindia: Telaah Pemikiran Kebangsaan, 2024)
The aim of this research is to understand the importance of innovation in history learning. This research uses the library research method. The research results show that innovation in history learning is clearly important to carry out because it has many benefits.